2003
DOI: 10.1016/s0014-5793(03)00930-x
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of hydrogen bonds in protein–RNA complexes for interaction patterns

Abstract: Structural analysis of protein^RNA complexes is labor-intensive, yet provides insight into the interaction patterns between a protein and RNA. As the number of protein^RNA complex structures reported has increased substantially in the last few years, a systematic method is required for automatically identifying interaction patterns. This paper presents a computational analysis of the hydrogen bonds in the most representative set of protein^RNA complexes. The analysis revealed several interesting interaction pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 15 publications
6
57
0
Order By: Relevance
“…Arginine-rich motifs (Weiss and Narayana 1998) are abundant in RNA binding sites, and other strong biases in the types of amino acids present in RNA-protein interfaces have been reported in several previous studies (Lustig et al 1997;Jones et al 2001;Kim et al 2003;Jeong et al 2004;Jeong and Miyano 2006). To evaluate whether these primary sequence biases can be effectively exploited in a machine learning approach to identify amino acid sequence correlates of RNA binding sites, we generated a nonredundant data set of 109 RNA binding proteins (see Materials and Methods) to estimate the interface propensity for each amino acid type as follows:…”
Section: Sequence Characteristics Of Rna Binding Sitesmentioning
confidence: 62%
See 1 more Smart Citation
“…Arginine-rich motifs (Weiss and Narayana 1998) are abundant in RNA binding sites, and other strong biases in the types of amino acids present in RNA-protein interfaces have been reported in several previous studies (Lustig et al 1997;Jones et al 2001;Kim et al 2003;Jeong et al 2004;Jeong and Miyano 2006). To evaluate whether these primary sequence biases can be effectively exploited in a machine learning approach to identify amino acid sequence correlates of RNA binding sites, we generated a nonredundant data set of 109 RNA binding proteins (see Materials and Methods) to estimate the interface propensity for each amino acid type as follows:…”
Section: Sequence Characteristics Of Rna Binding Sitesmentioning
confidence: 62%
“…In contrast, the number of experimentally determined structures for RNA-protein complexes is still relatively small and heavily biased (ribosomal proteins represent z50% of all RNA binding proteins in the Protein Data Bank [PDB]). Nevertheless, several computational analyses of RNA-protein complexes have generated databases of RNA-protein contacts and provided valuable insights into the biophysical basis of interaction patterns between ribonucleotides and amino acids (Cusack 1999;Draper 1999;Jones et al 2001;Kim et al 2003;Hoffman et al 2004;Jeong et al 2004;Jeong and Miyano 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the effect of different definitions of IP on the prediction performance, we encoded 3 different definitions of IP: the interaction propensity sIP of single nucleotides [7,10], the interaction propensity prev_tIP of nucleotide triplets, which is defined in a similar way as the IP of amino acid triplets used in our previous study [11], and the interaction propensity tIP of nucleotide triplets used in this study. The results shown in Table 3 were obtained by 5-fold cross validation with a window of 15 nucleotides.…”
Section: Interaction Propensity Of Nucleotide Tripletsmentioning
confidence: 99%
“…In previous studies, we performed an extensive analysis of the recent structures of protein-RNA complexes and computed several types of interaction propensity (IP) between amino acids and nucleotides [7,10,11]. Our analysis showed that the IP of amino acid triplets had a higher binding specificity than the IP of individual amino acids and that the IP of amino acid triplets was useful for predicting binding sites in proteins [11,12].…”
Section: Introductionmentioning
confidence: 97%
“…Since our previous study on hydrogen-bonding interactions between protein and RNA (Kim et al, 2003), the structures of many protein-RNA complexes have been determined. In this study we attempt a more rigorous study of the interactions by considering van der Waals interactions as well as hydrogen-bonding interactions in a new, extensive dataset of protein-RNA complexes.…”
Section: Introductionmentioning
confidence: 99%